Building a measure of institutional excellence for Iraqi sports clubs - mohammed AbdulJabbar Dr. Ahmed Raad (الرياضة المعاصرة)
Excellence is an integrated system based on modern management techniques and approaches, with the aim of raising performance and achievement levels to the highest levels, to outperform other organizations and to reach the global level. The current research aims to build a measure of the institutional excellence of Iraqi sports clubs, where the researcher in Title III used a set of scientific steps, where the researcher used the descriptive method on a sample of players participating in the Iraqi Premier League basketball, and was used by the mathematical medium and the standard deviation and the coefficient of simple correlation and the value of T-Test as appropriate statistical means. The researchers found a special measure that measures institutional excellence in Iraqi sports clubs.